Evaluating Land Management Options (ELMO): a participatory tool for assessing farmers’ sustainable land management decision preferences and trade-offs - Emerton, Lucy; Snyder, Katherine A.; Cordingley, Justine E. (2015)
This document provides guidance on applying the ELMO tool. It is primarily targeted at researchers seeking to collect information about the social and economic drivers of land use decisions, and wishing to investigate farmers’ sustainable land management preferences and trade-offs. As illustrated on the facing page, ELMO is organised around three basic questions, and entails 10 steps. Although these steps follow a logical, iterative process, it should be emphasised that the tool can be modified and adapted to the specific needs and context within which it is being applied. It is not always necessary to apply each and every step.